Effect of TGF‐β1 Superfamily Members on Survival of Buffalo (Bubalus bubalis) Embryonic Stem‐like Cells. Issue 4 (16th January 2013) - Sharma, R; Kamble, NM; George, A; Chauhan, MS; Singla, S; Manik, RS; Palta, P
Contents: This study examined the effects of supplementation of ES‐like cell culture medium with bone morphogenetic protein (BMP)‐4 (0, 10, 20 or 100 ng/ml) or Noggin (250, 500 or 750 ng/ml) or TGF‐β1 (0, 0.1, 1 or 10 ng/ml) or SB431542 (0, 10, 25 or 50 μm ), an inhibitor of TGF‐β1 signalling, on survival, colony area and expression level of pluripotency genes in buffalo ES‐like cells at passage 40–80, under different culture conditions. BMP‐4 supplementation significantly reduced (p < 0.05) colony survival rate, percentage increase in colony area and relative mRNA abundance of OCT4, whereas that of NANOG and SOX‐2 was increased significantly (p < 0.05). Noggin supplementation did not affect the colony survival rate and percentage increase in colony area in the presence of FGF‐2 and LIF. In the presence of FGF‐2 alone, it significantly reduced (p < 0.05) the relative mRNA abundance of OCT4 and SOX‐2 and increased (p < 0.05) that of NANOG . Supplementation with TGF‐β1 at 1.0 ng/ml but not at other concentrations increased colony survival rate but had no effect on percentage increase in colony area at any concentration. Supplementation with SB‐431542 decreased (p < 0.05) colony survival rate at 50 μm but not at other concentrations. The percentage increase in colony area was lower (p < 0.05) with 10 μm SB‐431542 than that in the controls, whereas at higher concentrations of 25 or 50 μm, SB‐431542 decreased (p < 0.05) the colony size instead of increasing it. In conclusion, these results suggest that BMP‐4 induces differentiation in buffalo ES‐like cells, whereas TGF‐β/activin/nodal pathway may not be playing a crucial role in maintaining pluripotency in these cells.